ANALISIS RISIKO DAN RETURN PORTOFOLIO REKSADANA DI INDONESIA 2009-2011 - , Mohamad Arief ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research planned to analyze risk and return any type of mutual funds consisting of stock fund, bond fund, hybrid fund and money market mutual fund in Indonesia in the period 2009 to 2011. By analyzing the risk and return any type of mutual fund uses historical data, it could be used to predict and determine the best mutual funds of every type of mutual funds in the future. To determine the best mutual funds of any kind used Sharpe Ratio measurement. By Sharpe Ratio measurement, it could be made 10 mutual funds ranking from the best to the worst of any type of mutual funds. After creating a ranking of mutual funds of any kind using Sharpe Ratio measurement, it would be reformed every type of mutual funds rankings based on the highest return is used to create a portfolio that combines four types of mutual funds with various combinations. Results of various combinations of the portfolio, it would be adjusted to the characteristics of the type of risk investors so as to produce an optimal portfolio. This research discusses the concept of wealth management to the second pillar is wealth growth & accumulation focused on the financial asset instrument in mutual fund investment. The final result of this research is some investment advices on mutual fund portfolio options adjusted to the characteristics of the type of risk investors.